The ottoman turkish in teaching - Ulucan, Mehmet (T.C. Milli Egitim Bakanligi, 2016)
Man is a continually learning being. Language underlies learning. From the very beginning, language has played a very important role in all achievements of humanity. Developments in the fields and disciplines of science, art and education have been achieved thanks to the language. Yet language is also a reality that is learnt and taught. Our language, Turkish, has made substantial contribution to all fields in the past and this day. This contribution should continue in the future as well. Therefore, Turkish language, as a developed language, should be at the heart of all changes and developments in all fields and gain a place among the languages which need to be taught and learnt in Turkey and in the world. While trying to achieve this mission, Turkish language should use its all past experiences. In other words, all periods of Turkish language should be taken into consideration. Also, all achievements and experiences pertaining to the period of Ottoman Turkish should be utilized. Accordingly, Ottoman Turkish should also be taken into account when learning and teaching the Turkish language in Turkey and in the world. This study focuses on the place and importance of Ottoman Turkish in learning and teaching the Turkish language abroad.
Osmanli türkçesinin öğretimi
Keywords: Ottoman turkish; Ottoman turkish in teaching; Turkish